ArcGIS StoryMaps as Geography Teaching Materials for the Distribution of Indonesian Flora and Fauna at Senior High School - Muhammad Taufan Nuryadin; Sugeng Utaya; I Komang Astina (Universitas Negeri Gorontalo, 2025)
The diversity of teaching materials in the current era is experiencing very rapid development, so that the selection of appropriate teaching materials will have an impact on student learning outcomes. The purpose of this study was to analyze the results of the application and determine the improvement in student learning outcomes in the implementation of teaching materials based on ArcGIS StoryMaps. The results of initial observations conducted at SMA Negeri 12 Makassar showed that teachers still use teaching materials in the form of books, power points and websites that are less interactive so that this has an impact on student learning outcomes that are lacking. The method in this study uses N-Gain analysis to measure student learning outcomes. The data collection technique in this study was divided into two classes, namely the experimental class and the control class with 20 samples each through pre-test and post-test. The results of this study are 1. based on the results of the average pre-test, the experimental class score was 52 and the control class 34 while the average post-test score in the experimental class was 73 and the control class 35. 2. Based on the results of the normality test (N-Gain) showed that the experimental class was 0.56 and the control class was 0.8. This shows that there has been an increase in students' understanding in the use of teaching materials based on ArcGIS StoryMaps, especially in the material on the Distribution of Flora and Fauna in Indonesia